LEARNING LOCAL WISDOM IN ELEMENTARY SCHOOL THROUGH MAJAPAHITAN STATUE - Putri Rachmadyanti; Aristya Nuraini; Wiryanto Wiryanto (Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study discusses one of the famous cultural products in East Java, namely the Majapahitan Statue from Mojokerto. The purpose of this study is to analyze the material contained in the Majapahitan Statue to support the development of local wisdom-based learning in Elementary Schools. The existence of The Mojopahitan Statue can be developed as a learning resource for thematic learning in accordance with the 2013 Curriculum to develop the competence of Elementary School Students comprehensively. The research using a qualitative approach with data collection techniques using interviews and observations. The values contained in the Majapahitan Statue were developed into a Learning Plan with a scientific approach. The Majapahitan statue contains the value of knowledge about history, natural resource, location. Affective aspects that can be obtained by students are learning about cooperation, discipline, and creativity. The psychomotor aspect includes skills in making reports about Majapahitan statues. Learning local wisdom is also a form of developing contextual learning that utilizes the environment as a source of student learning.